(untitled) (Indian Journal of Animal Production and Management, 2016)
A synthetic breed named as “Nellore Synthetic” was evolved at Livestock Research Station, Palamaner, Andhra Pradesh was developed by crossing of the Nellore sheep of Andhra Pradesh with the exotic breeds of Dorset and Suffolk by stabilizing the exotic inheritance at 50%. Data on various body weights were subjected to least square analysis of variance by using fixed effect model to estimate the effect of various non genetic factors Data on various body weights were subjected to least square analysis of variance by using fixed effect model to estimate the effect of various non genetic factors. Overall mean birth weight of Nellore sheep at birth, weaning, 6, 9 and 12 months of age were 3.40±0.02 kg, 13.35±0.07kg, 17.78±0.09 kg, 20.03±0.11 kg and 22.47±0.12 kg respectively. All body weights were significantly (P<0.01) influenced by season of birth, year and sex of lamb. Lambs born during off season were significantly (P<0.01) heavier than the lambs born during main season. The results of present investigations indicated that, body weights at different ages in Nellore sheep were significantly (P<0.01) influenced by year, season of birth and sex and hence selection based on such traits might lead to enhancement of overall improvement of production as well as growth traits in Nellore synthetic sheep breed.